Efficacy and safety of subcutaneous injection of botulinum toxin in the treatment of Chinese postherpetic neuralgia compared to analgesics: a systematic review of randomized controlled trials and meta-analysis - Wang, Hui; Lin, Ping (Frontiers in Neurology, 2024)
Objective. The purpose of this meta-analysis is to investigate the efficacy and safety of subcutaneous injection of botulinum toxin in the treatment of postherpetic neuralgia compared to analgesics. Methods. We searched PubMed, Cochrane Library, Embase, Web of Science, Chinese National Knowledge Infrastructure (CNKI), and Wanfang for randomized controlled trials from inception to September 10, 2023. Primary clinical outcomes included VAS pain scores and clinical effective rate. The secondary clinical outcome is the adverse event rate during follow-up. Results. A total of 14 studies with 1358 participants were subjected to meta-analysis. Among all included patients, 670 participants received botulinum toxin A injection and 688 participants received other medication treatment. BTX-A group exhibited lower pain scores (week 2: MD: -1.91; 95% CI: -2.63 to -1.20; P<0.00001; week 4: MD: -1.69; 95% CI: -2.69 to -0.68; P<0.00001; week 8:MD: -1.66; 95% CI: -2.20 to -1.12; P<0.00001; week 12:MD: -1.83; 95% CI: -2.70 to -0.96; P<0.00001;week 24: MD: -1.07; 95% CI: -1.16 to -0.99; P<0.00001). The effective rate was significantly higher in patients who received BTX-A for postherpetic neuralgia compared to those who received lidocaine or gabapentin (lidocaine: MD: -1.55; 95% CI: -2.84 to -0.27; P=0.02; gabapentin: MD: -1.57; 95% CI: -2.12 to -1.02; P<0.00001). There was no difference in the incidence of adverse events between the treatment groups (OR 1.25, 95% CI 0.43 to 3,61, P=0.69). Conclusion. Our meta-analysis showed that BTX-A has certain advantages in relieving postherpetic neuralgia compared to analgesics. Meanwhile, BTX-A is safe for treating postherpetic neuralgia, without notable side effects.